2023
DOI: 10.1038/s41598-023-41304-0
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of foraging behavior in neotropical stingless bees using pollen and honey metabarcoding

Aline C. Martins,
Carolyn E. B. Proença,
Thais N. C. Vasconcelos
et al.

Abstract: Stingless bees are major flower visitors in the tropics, but their foraging preferences and behavior are still poorly understood. Studying stingless bee interactions with angiosperms is methodologically challenging due to the high tropical plant diversity and inaccessibility of upper canopy flowers in forested habitats. Pollen DNA metabarcoding offers an opportunity of assessing floral visitation efficiently and was applied here to understand stingless bee floral resources spectra and foraging behavior. We ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Myrtaceae species are dominant in many different kinds of Neotropical ecosystems, such as lowland Atlantic Forest (Staggemeier et al, 2017), rocky outcrop savanna (Santos et al, 2012), high altitude cloud forest and riverine forests (Ibisch et al, 2002). Besides composing a significant part of the biomass that forms these ecosystems, they offer flower resources to pollinators and fleshy-fruits to frugivores and insects (Gressler et al, 2006; Valadão et al, 2019; Martins et al, 2023), which are produced throughout all seasons of the year (Staggemeier et al, 2010, 2015a, 2017). Some species are a promising source of biologically active compounds with medicinal properties such as antimicrobial, antilarval, antioxidant, anti-inflammatory, and cytotoxic (Stefanello et al, 2011; Cascaes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Myrtaceae species are dominant in many different kinds of Neotropical ecosystems, such as lowland Atlantic Forest (Staggemeier et al, 2017), rocky outcrop savanna (Santos et al, 2012), high altitude cloud forest and riverine forests (Ibisch et al, 2002). Besides composing a significant part of the biomass that forms these ecosystems, they offer flower resources to pollinators and fleshy-fruits to frugivores and insects (Gressler et al, 2006; Valadão et al, 2019; Martins et al, 2023), which are produced throughout all seasons of the year (Staggemeier et al, 2010, 2015a, 2017). Some species are a promising source of biologically active compounds with medicinal properties such as antimicrobial, antilarval, antioxidant, anti-inflammatory, and cytotoxic (Stefanello et al, 2011; Cascaes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although we deal with 'snapshots' of spring and summer networks, we will deepen the reflection on the likely effects of the intraannual dynamics of interactions on the networks structure, based on two striking aspects of the foraging behaviour and ecology of stingless bees: on one hand, adaptive foraging expressed in the ability to make choices of food sources (e.g., Schmidt et al, 2006;Martins et al, 2023), based on the cost-benefit of foraging (as demonstrated experimentally, mainly with A. mellifera; e.g., Davies et al, 2012), and the ability to develop temporary floral constancy and preference (Hrncir et al, 2019;Kleinert et al, 2009;Ramalho, 1990;Ramalho, 2004); and on the other hand, the competitive structure of their assemblages (Biesmeijer & Slaa, 2006;Johnson & Hubbell, 1974;Kleinert et al, 2009;Kleinert & Giannini, 2012), which generates diffuse foraging pressure on other pollinators. To this end, we explored theoretical arguments from two structural models that are characterised by analysing the effects of adaptive foraging dynamics and competition between generalists and specialists (Bastolla et al, 2009;Valdovinos, 2019;Valdovinos et al, 2016) on the structure of mutualist networks.…”
Section: Introductionmentioning
confidence: 99%
“…One of the dominant components in these environments are the myrtles (Myrtaceae), a group of trees and shrubs of outstanding diversity and abundance in both neotropical rainforests and savannas (Mori, 1983;Oliveira-Filho and Fontes, 2000;Ibisch et al, 2002;Zipparro et al, 2005;Mendonça et al, 2008;Joly et al, 2012;Santos et al, 2012;Françoso et al, 2016;Staggemeier et al, 2017). Besides comprising a significant part of the biomass that forms these ecosystems, Myrtaceae species are an important source of floral resources and fleshy-fruits, which are produced throughout all seasons of the year (Staggemeier et al, 2010(Staggemeier et al, , 2015a(Staggemeier et al, , 2017, to pollinators and frugivores in the region (Gressler et al, 2006;Valadão et al, 2019;Martins et al, 2023). Some species are also a promising source of biologically active compounds with medicinal properties such as antimicrobial, antilarval, antioxidant, anti-inflammatory, and cytotoxic (Stefanello et al, 2011;Cascaes et al, 2015).…”
mentioning
confidence: 99%